2021
DOI: 10.1007/s11366-020-09710-7
|View full text |Cite
|
Sign up to set email alerts
|

The Struggle for Certainty: Ontological Security, the Rise of Nationalism, and Australia-China Tensions after COVID-19

Abstract: Australia-China relations have been relatively stable over the last decade. However, soon after the outbreak of COVID-19, Australia took an increasingly assertive stance toward China, one that is arguably even more assertive than those of its Western allies. What prompted Australia to adopt a tougher policy against China? This article argues that COVID-19 has brought significant uncertainty to the international system and, hence, to Australia's external environment, which has affected the country's decisionmak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 30 publications
(26 reference statements)
1
14
0
Order By: Relevance
“…The rise of nationalism on a global scale during COVID-19 has become a big concern [ 8 , 20 , 21 , 28 34 ]. While the nationalist sentiment reflected in the debate about the Wuhan Diary has been most intense in China, it sent ripples through Chinese communities worldwide.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rise of nationalism on a global scale during COVID-19 has become a big concern [ 8 , 20 , 21 , 28 34 ]. While the nationalist sentiment reflected in the debate about the Wuhan Diary has been most intense in China, it sent ripples through Chinese communities worldwide.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Despite facing identical information, people can form different opinions. This can be attributed to motivated reasoning and beliefs , which refers to the psychological phenomenon that people choose to believe what they want to believe [ 3 , 20 , 21 ]. One notable example is the impact of identity attachment on belief formation.…”
Section: Social Identity Group Criticism Motivated Beliefs: a Literature Reviewmentioning
confidence: 99%
“…Previous studies have reported that the lack of ontological security could promote people's risk-taking tendency among migrant workers ( 12 ). In addition, the research in Australia illustrated that the concerns about the uncertainties of the future created by the COVID-19 crisis might trigger ontological insecurity ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 outbreak has significantly brought a kind of anti-mobility/anti-globalisation tendency all over the world [51,58]. The re-localisation in urban China, however, is not the same as the rise of nationalism and localism in western countries, for instance, rejecting global trade and the empowerment of the local government, during the pandemic [33,59]. They share some common characteristics, such as restricted cross-regional physical mobility and the revaluation of the "local".…”
Section: The Location-based Governing System and Paradoxical Mobilitiesmentioning
confidence: 99%